Microalgal and cyanobacterial bioactives: Promising candidates for next-generation nutraceuticals - L. Inbathamizh; Elanthendral Gopalsami; Srishti Raja; Aswini Sai Balaji; Pooja Nath; P. Jayameenaa; Prakash Pandurangan (Food and Humanity, 2026)

Highly dispersed Cu on TiO₂ for photoreduction of hexavalent chromium in the presence of glycerol - Srishti; Shweta Kumari; Sumit Kumar Pathak; Abhishikta Chatterjee; Varun Kumar Gupta; Aditya Kumar; Apurba Sinhamahapatra (Journal of Environmental Chemical Engineering, 2026)

Historic drought in northern Kenya shifts diet and mobility away from traditional pastoralism as resource security and nutrition falter - Asher Y. Rosinger; Matthew Douglass; Amanda McGrosky; Kedir Teji Roba; Benjamin Davies; Natalie Meriwether; Alfredo J. Rojas; Leslie Ford; Hannah Jacobson; Faith Wambua; Elena Hinz; Srishti Sadhir; et al. (Global Environmental Change, 2026)

Cork–polypropylene composites for food contact: a comprehensive study of morphology, migration, chemical safety, and sensory analysis - Tiago Vieira; Cláudia Marques; Srishti Singh; Susana Teixeira; Patrícia Guerreiro; Joel Pereira; Maria Selbourne; Lisete Moutinho; Clara Sousa; Fátima Poças (Food Additives & Contaminants: Part A, 2026)

Developmental block in ruminant embryos: Mechanisms, molecular insights and potential interventions - Srishti Bhatia; Manu Mangal; Priya Dahiya; Ashish Sindhu; Bhavya Maggo; Meeti Punetha; Prasoon Priyadarshi; Manoj Kumar Jena; Dharmendra Kumar (Animal Reproduction Science, 2026)

Coevolutionary analysis-driven design of a p53 neoantigen multi-epitope peptide vaccine for lung cancer immunotherapy - Komal Kumari; Gyan Prakash Rai; Manaswini Jagadeb; Srishti Shriya; Nooruddin Khan; Vinay Kumar; Asheesh Shanker; Rizwanul Haque (In Silico Pharmacology, 2026)

Retraction notice to “Biochar for urban agriculture: Impacts on soil chemical characteristics and on Brassica rapa growth, nutrient content and metabolism over multiple growth cycles” [Sci. Total Environ. 727 (2020) 138742] - Shuang Song; Srishti Arora; Anna Karen C. Laserna; Ye Shen; Brian W.Y. Thian; Jia Chin Cheong; Jonathan K.N. Tan; Zhongyu Chiam; Siew Lee Fong; Subhadip Ghosh; Yong Sik Ok; Sam F.Y. Li; et al. (Science of The Total Environment, 2026)

Revealing Pesticide-Adapted Soil Microbiome through Shotgun Metagenomics - Srishti Sinha Ray; Nishu Goyal; Abhishek Gupta; Sanjay Swarup; Durga Madhab Mahapatra (Bioresource Technology Reports, 2026)

Elucidating the Functional Role of PGPR in Modulating Plant Physiology for Improved Drought Resilience and Yield Enhancement: A Review - Srishti Mishra; Krishna Kumar Choudhary (Journal of Soil Science and Plant Nutrition, 2026)

Insights into the 2025 Mw 7.7 Myanmar Earthquake using the broadband ground motion simulations - Jahnabi Basu; Srishti Kushwaha; S. T. G. Raghukanth (Journal of Seismology, 2026)

Somatic embryogenesis, secondary somatic embryogenesis and plant regeneration in Dillenia indica L., an underutilized fruit tree - Amit Singh; Srishti Yadav; Manoj K. Rai (In Vitro Cellular & Developmental Biology - Plant, 2026)

Assessing soil microbiome alterations in agricultural land exposed to pesticides through amplicon-based sequencing - Srishti Sinha Ray; Nishu Goyal; Madhumita Bhattacharyya; Smriti Arora; Kanchan Deoli Bahukhandi; Durga Madhab Mahapatra (Biodegradation, 2026)

In vitro propagation of Dillenia pentagyna Roxb.: a medicinal tree with high conservation priority - Amit Singh; Srishti Yadav; Manoj K. Rai (Vegetos, 2026)

Radical Quenching and LOX Inhibiting Properties of Indole Derivatives: A Plausible Mechanism of Action Through HAT, SET-PT and SPLET Pathway - Km Srishti; Oseen Negi; Anamika Gusain; Naresh Kumar; Rahul Kumar Vishwakarma; Prasanta Kumar Hota (Journal of Fluorescence, 2026)

Fabrication, characterization, and performance of microalgae-hydrocolloid stabilized inks for 3D printing applications - Bhawna Bisht; Akuleti Saikumar; Nitigya Verma; Srishti Nagrath; Akshansh Sharma; Anna Kurbatova; Laxmikant S. Badwaik; Mikhail S. Vlaskin; Sanjay Kumar; Vinod Kumar (Food and Humanity, 2026)

A semantic framework for chemical process digitalisation using ontologies - Shuyuan Zhang; Yong Ren Tan; Cuong Manh Nguyen; Dogancan Karan; Srishti Ganguly; Nicholas Jose; Mei Qi Lim; Shuqiao Guo; Lianlian Jiang; Markus Kraft; Alexei A. Lapkin (Chemical Engineering Journal, 2026)

Deciphering the differential response of naturally growing species to metal-induced stress across various land uses - Srishti Mishra; Shashi Bhushan Agrawal; Madhoolika Agrawal (Ecotoxicology, 2026)

Cardiovascular Health and Fluoride Toxicity: A Qualitative Systematic Review - Rashi Baltoo; Ruhi Thakur; Srishti Rana (Cardiovascular Toxicology, 2026)

Lipoxygenases: The gatekeepers in plant resilience against biotic stress - Manisha Yadav; Srishti Satija; Saurabh Awasthi; Indrakant K. Singh; Archana Singh (Plant Gene, 2026)

Eco-friendly mycelium composites: Redefining vegan leather for a greener future - Srishti Tewari; Shamlan M.S. Reshamwala; Ravindra D. Kale (Biomass and Bioenergy, 2026)

Fabrication of Cotton-Mycelium based Biocomposite (CMBB) via submerged fermentation for sustainable vegan leather: a novel green approach - Srishti Tewari; Preeti Singh; Shamlan M.S. Reshamwala; Latika Bhatt; Ravindra D. Kale (Bioresource Technology, 2026)

Drinking water quality assessment through multivariate statistical approach and formulated PCA-based contamination index - Srishti Srivastava; Abdul Malik (Journal of Contaminant Hydrology, 2026)

Cold plasma pretreatment enhances OSA esterification efficiency in Kodo millet starch: Morphological, structural, rheological, and functional insights - Yograj Bist; Mohit Nagar; Yogesh Kumar; Srishti Upadhyay; D.C. Saxena; Vijay Singh Sharanagat (Innovative Food Science & Emerging Technologies, 2026)

Recent advances and research trends in phytoremediation of polycyclic aromatic hydrocarbons (PAHs): A critical review - Nitu Gupta; Apurba Koley; Srishti Debnath; Arunkumar Patchaiyappan; Komal Kumari; Lubana Ishrat; Chandrani Sinha Roy; Srinivasan Balachandran; Raza Rafiqul Hoque (Applied Soil Ecology, 2026)

Potential of India’s AFOLU sector in achieving net zero: A systematic review of land-based mitigation strategies - Srishti Gwal; Aditya Sharma; Andrew Pascale; Rajarshi Dasgupta; Ganesh Hegde; Chris Greig (Land Use Policy, 2025)

Nanostructured Lipid Carriers of Mycophenolate Mofetil: Quality by Design Enabled Formulation Development and In-Vitro Evaluation - Srishti Naryal; Shagun Katoch; Ashish Baldi (Journal of Pharmaceutical Innovation, 2025)

A curated tissue-specific proteome, phosphoproteome, and kinome map of Drosophila melanogaster with an integrated outlook in circadian physiology - Sandip Das; Arpita Kannihalli; Srishti Banerjee; Nikita Chakraborty; Sandipan Ray (Functional & Integrative Genomics, 2025)

In vitro propagation, phytochemical analysis and assessment of antioxidative potential of micropropagated plants of Tecomaria capensis (Thunb.) Spach - Srishti Yadav; Amit Singh; Madan Mohan; Subha Narayan Das; Manoj K. Rai (South African Journal of Botany, 2025)

Strontium manganese-based bimetallic oxide cathode catalyst for enhanced power production and desalination in microbial desalination cell - Srishti Mishra; Gourav D. Bhowmick; Brajesh K. Dubey; Makarand M. Ghangrekar (Desalination, 2025)

Current usage of paperboard packaging: A case study of the European landscape on tomato packaging - Srishti Singh; Ece Sögut; Ilke Uysal-Unalan; Igor Karlovits; Véronique Coma; Milena Corredig; Fátima Poças (Food Packaging and Shelf Life, 2025)

Quinoxaline Based Three Channel Fluorescent-colorimetric Chemosensor for Selective and Sensitive Detection of Ag+ Ions: Biological and Environmental Applications - Srishti Dutta; Vanshika Sharma; Abhilash Pandey; Dishen Kumar; Devanand Sahu; Goutam Kumar Patra (Journal of Fluorescence, 2025)

Unveiling the microstructural dynamics of Pickering emulsions: A microrheological approach - Gourav Chakraborty; Srishti Upadhyay; Vijay Singh Sharanagat; Jasim Ahmed (Food Research International, 2025)

Synergic valorization of nickel-chrome plating sludge via alkali activation of steel slag and fly ash: performance analysis - Anant Mishra; Gaurav Tyagi; Srishti Khare; Mukund Lahoti; Anupam Singhal; Srikanta Routroy; Dipendu Bhunia; Steven G. Sachs; Alessandro F. Rotta Loria (Clean Technologies and Environmental Policy, 2025)

Exploring fluoride's role in diabetes development: A review - Ruhi Thakur; Srishti Rana; Rashi Baltoo (Journal of Trace Elements in Medicine and Biology, 2025)

Green and sustainable Pd-Co nanoparticle assisted electroless copper-Plated cotton fabric for multifaceted catalytic and antimicrobial applications - Akanksha Sood; Srishti; Navneet Kaur; Bunty Sharma; Rajeev Kumar; K.K. Bhasin; Jaspreet S. Dhau; Ganga Ram Chaudhary (Journal of Cleaner Production, 2025)

Geospatial mapping and cluster analysis of antibiotic-resistant Escherichia coli in drinking water of semi-arid areas - Srishti Srivastava; Akshay Kumar; Rajiv Gupta; Abdul Malik (Environmental Monitoring and Assessment, 2025)

Bio-chelation for sustainable heavy metal remediation in municipal solid waste compost: A critical review of chelation technologies - Srishti Khare; Anupam Singhal; Srinivas Rallapalli; Anant Mishra (Environmental Science and Pollution Research, 2025)

Studies on genetic variability and character association for green pod yield and component horticultural traits in garden pea (Pisum sativum L.) under North-Western Himalayas - Shimalika Sharma; Akhilesh Sharma; Srishti (Vegetos, 2025)

Intensity-based seismic hazard assessment and zone map of India using SASHA approach - Narsiram Gurjar; Ravi Kanth Sriwastav; Srishti Kushwaha; S. T. G. Raghukanth (Stochastic Environmental Research and Risk Assessment, 2025)

Meta-Topolin-Mediated Plant Regeneration in Giant Granadilla (Passiflora quadrangularis L.): An Underutilized Fruit Crop - Roshni Rathour; Srishti Yadav; Amit Singh; Sandeep Kaushik; Manoj K. Rai (Applied Fruit Science, 2025)

Comprehensive assessment of leaching characteristics in electric arc furnace slag-based alkali-activated mortar - Anant Mishra; Srishti Khare; Nagapradeep Nidamanuri; Mukund Lahoti (Environmental Science and Pollution Research, 2025)

Tannins as Therapeutic in Managing Obesity and Beyond - Ankul Singh S; Rukaiah Fatma Begum; Srishti Singh; Thirumal Margesan (Current Pharmacology Reports, 2025)

Examining the Influence of Green Human Resource Practices on Organisational Citizenship Behaviour for Environment in Indian Banking: mediating role of green crafting through JD-R theory perspectives - Srishti Garg; Ritu Gandhi Arora (Environment, Development and Sustainability, 2025)

Taxonomic treatment of the genus Arctelene Kirti & Gill 2008 (Erebidae: Arctiinae) with description of two new species from India - Santosh Singh; Srishti Bhattacharya; Navneet Singh; Jagbir Singh Kirti (International Journal of Tropical Insect Science, 2024)

Harnessing insects mediated plastic biodegradation: Current insight and future directions - Jasti Sri Vishnu Murthy; Alagesan Keerthana; K. Logeswaran; Abhibandana Das; Srishti Choudhury; Bindu Gudi Ramakrishna; Sanhita Chowdhury; Himani Aggarwal; S. Saravanan; Arindam Pal; Vinod Kumar Dubey; Vinay Kumar (Journal of Environmental Management, 2024)

Development of Land Use Regression (LUR) models and high-resolution spatial mapping of criteria air pollutants: Leveraging Delhi's continuous air monitoring network and remote sensing data - Pratyush Agrawal; Adithi R. Upadhya; Srishti S; Mahesh Kalshetty; Padmavati Kulkarni; Meenakshi Kushwaha; V. Sreekanth (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Exploring the viability of anti-microbial, superhydrophobic jute bags as an approach to sustainable food packaging system - Srishti; Aditya Kumar (Food Chemistry, 2024)

Integrated fuel cell system for sustainable wastewater treatment, ammonia recovery, and power production - Anil Dhanda; Lakshmi Pathi Thulluru; Srishti Mishra; Shamik Chowdhury; B.K. Dubey; Makarand M. Ghangrekar (Environmental Research, 2024)

Versatility of reverse transcriptase loop-mediated isothermal amplification (RT-LAMP) from diagnosis of early pathological infection to mutation detection in organisms - Srishti Sen; Priyanka Bhowmik; Shubhangi Tiwari; Yoav Peleg; Boudhayan Bandyopadhyay (Molecular Biology Reports, 2024)

Alterations in Circadian Rhythms, Sleep, and Physical Activity in COVID-19: Mechanisms, Interventions, and Lessons for the Future - Sandip Das; Rajni Khan; Srishti Banerjee; Shashikant Ray; Sandipan Ray (Molecular Neurobiology, 2024)

WGS-based screening of the co-chaperone protein DjlA-induced curved DNA binding protein A (CbpA) from a new multidrug-resistant zoonotic mastitis-causing Klebsiella pneumoniae strain: a novel molecular target of selective flavonoids - Mohammad Habibur Rahman; Salauddin Al Azad; Mohammad Fahim Uddin; Maisha Farzana; Iffat Ara Sharmeen; Kaifi Sultana Kabbo; Anika Jabin; Ashfaque Rahman; Farhan Jamil; Sanjida Ahmed Srishti; Fahmida Haque Riya; Towhid Khan; et al. (Molecular Diversity, 2024)

Potential of sensing interventions in the life cycle assessment of fruits and fruit juices - Pawankumar Rai; Srishti Mehrotra; Sandeep K. Sharma (Trends in Food Science & Technology, 2024)

Cellulose trays with PLA-based liners as single-used food packaging: Characterisation, performance and migration - Amaury Furet; Srishti Singh; Christian Gardrat; Léna Alembik; Ronan Jaouannet; Fátima Poças; Véronique Coma (Food Packaging and Shelf Life, 2024)

Synergistic insights into pesticide persistence and microbial dynamics for bioremediation - Srishti Sinha Ray; Kashish Parihar; Nishu Goyal; Durga Madhab Mahapatra (Environmental Research, 2024)

Soil Microbiome and its Functional Attributes Under the Gradient of Arsenic Contamination in Paddy Soils - Mariya Naseem; Praveen C. Verma; Richa Raghuwanshi; Vivek K. Gaur; Manisha Singh; Srishti Seth; Pankaj Kumar Srivastava (Water, Air, & Soil Pollution, 2024)

Fluorescence Spectroscopic Studies to Evaluate Binding Interaction between Hoechst 33258 and Bilirubin - Srishti Singh Chauhan; Bhaskar Mohan Murari (Journal of Fluorescence, 2024)

A review on therapeutic potential of wild mushrooms with their relative status in Chhattisgarh, Central India - Srishti Verma; Samay Tirkey; Kamlesh Shukla (Advances in Traditional Medicine, 2024)

Fluoride-Induced Alterations in the Pancreas of Mammals: A Meta-analysis - Srishti Rana; Neha Thakur; Ruhi Thakur (Biological Trace Element Research, 2024)

Enhancing electrokinetics and desalination efficiency through catalysts and electrode modifications in microbial desalination cells - Srishti Mishra; Anil Dhanda; Brajesh K. Dubey; Makarand M. Ghangrekar (Journal of Environmental Management, 2024)

Distinct microbial communities enriched in water-saturated and unsaturated reactors influence performance of integrated hydroponics-microbial electrochemical technology - Ravi K. Yadav; Srishti Chaudhary; Sunil A. Patil (Bioresource Technology, 2024)

Agricultural watershed conservation and optimization using a participatory hydrological approach - Shubham Aggarwal; Srinivas Rallapalli; Nithyasree Thinagaran; Aravindh Sabarish Bakthavatchalam; Srishti Khare; Joe Magner (Environmental Science and Pollution Research, 2024)

A systematic review of diet and medication use among centenarians and near-centenarians worldwide - Zhaoli Dai; Sue Yi Lee; Srishti Sharma; Shahid Ullah; Edwin C. K. Tan; Henry Brodaty; Aletta E. Schutte; Perminder S. Sachdev (GeroScience, 2024)
Centenarians represent a phenomenon of successful aging. This systematic review aimed to understand lifestyles and health practices, focusing on diet and medication use for healthy longevity in community-based adults 95 years or over. Medline, CINAHL, Scopus, and gray literature were searched from 1 January 2000 to 10 December 2022. Study quality was assessed using the Modified Newcastle-Ottawa Scale (mNOS). Pooled prevalence [%; 95% confidence interval] for categorical variables and pooled mean for continuous variables were estimated for demographics, weight status, lifestyle factors, medications, and health conditions. Of 3392 records screened, 34 studies were included in the review, and 71% (24/34) met the 6/8 criteria in mNOS. Centenarians/near-centenarians’ ages ranged from 95 to 118 years, with 75% (71–78%) female and 78% (68–88%) living in rural areas. They had an overall healthy lifestyle: current smoking (7%; 5–9%), drinking (23%; 17–30%), normal weight (52%; 42–61%), overweight (14%; 8–20%), physical activity (23%; 20–26%), and sleep satisfaction (68%; 65–72%). Diet averaged 59.6% carbohydrate, 18.5% protein, and 29.3% fat; over 60% consumed a diverse diet, and < 20% preferred salty food, contributing to lower mortality risks and functional decline. About half used antihypertensives (49%; 14–84%) or other cardiovascular drugs (48%; 24–71%), with an average of 4.6 medications. Common health issues included impaired basic activities of daily living (54%; 33–74%), hypertension (43%; 21–65%), and dementia (41%; 23–59%). The findings of this systemic review underscore the pivotal role of dietary practice and weight management in healthcare strategies to promote healthy ageing. It also recognises rural living styles and sleep hygiene as potential factors contributing to healthy longevity.

A silent revolution: Rapid rise of cycling to school in rural India - Srishti Agrawal; Adit Seth; Rahul Goel (Journal of Transport Geography, 2024)

Safety profile of ZnO active packaging PBAT based biomaterial for food packaging. First tier evaluation - Srishti Singh; Joel Pereira; Patricia Guerreiro; Céu Selbourne; Cidália Paula; António Cunha; Clara Sousa; Fátima Poças (Food Control, 2024)

Recycling electric arc furnace slag through tailoring of ambient-cured alkali-activated mortar mix using hybrid AHP-GRA and TOPSIS - Anant Mishra; Mukund Lahoti; Srishti Khare; En-Hua Yang (Journal of Cleaner Production, 2024)

Explainable machine learning for predicting stomatal conductance across multiple plant functional types - Srishti Gaur; Darren T. Drewry (Agricultural and Forest Meteorology, 2024)

State-of-the-art of biochar amended dark fermentative hydrogen production: A sustainable coupling of decarbonization pathways towards low carbon future - Srishti Roychowdhury; Shiladitya Ghosh (Journal of Cleaner Production, 2024)

Trend Analysis for Different Types of Aerosols in Conjugation with Temperatures for the Indian Region During the Post-monsoon Season (1980–2019) - Harsh Yadav; Manu Mehta; Shruti Jain; Sandhya Singh; Srishti Bhandari; Seema Nihalani (Aerosol Science and Engineering, 2024)

Recent Development on Copper-Sensor and its Biological Applications: A Review - Km Srishti; Oseen Negi; Prasanta Kumar Hota (Journal of Fluorescence, 2024)

Let us take a walk to the sustainable tourism practices: a qualitative study through the lens of tourism experts - Vikas Arya; Vilte Auruskeviciene; Srishti Agarwal; Priyanka Kokatnur; Harish Kumar; Rajeev Verma (Environmental Science and Pollution Research, 2024)

Endophytic Alkalotolerant Plant Growth-Promoting Bacteria Render Maize (Zea mays L.) Growth Under Alkaline Stress - Srishti Kar; Shashank Kumar Mishra; Sankalp Misra; Renuka Agarwal; Susheel Kumar; Puneet Singh Chauhan (Current Microbiology, 2024)

An Updated Trial Sequential Meta-analysis of Vitamin D Receptor Gene Polymorphism (Fok1, Bsm1, Taq1 and Apa1) and Risk to Tuberculosis - Srishti Shah; Priyanka; Sadhna Sharma (Indian Journal of Clinical Biochemistry, 2024)

Assessment of herbaceous community structure for identifying metal-tolerant species at different land uses in and around Varanasi city - Srishti Mishra; Shashi Bhushan Agrawal; Madhoolika Agrawal (Environmental Science and Pollution Research, 2023)

Vegan leather: a sustainable reality or a marketing gimmick? - Srishti Tewari; Shamlan M. S. Reshamwala; Latika Bhatt; Ravindra D. Kale (Environmental Science and Pollution Research, 2023)

Sustainable approach to oil recovery from oil spills through superhydrophobic jute fabric - Srishti; Aditya Kumar (Marine Pollution Bulletin, 2023)

Evaluating fire resistance of timber columns using explainable machine learning models - Mohsen Zaker Esteghamati; Thomas Gernay; Srishti Banerji (Engineering Structures, 2023)

Oncoinformatic screening of the gene clusters involved in the HER2-positive breast cancer formation along with the in silico pharmacodynamic profiling of selective long-chain omega-3 fatty acids as the metastatic antagonists - A K M Helal Morshed; Salauddin Al Azad; Md. Abdur Rashid Mia; Mohammad Fahim Uddin; Tanzila Ismail Ema; Rukaiya Binte Yeasin; Sanjida Ahmed Srishti; Pallab Sarker; Rubaita Younus Aurthi; Farhan Jamil; Nure Sharaf Nower Samia; Partha Biswas; et al. (Molecular Diversity, 2023)

Source apportionment, health risk assessment, and trajectory analysis of black carbon and light absorption properties of black and brown carbon in Delhi, India - Vikas Goel; Srishti Jain; Vikram Singh; Mayank Kumar (Environmental Science and Pollution Research, 2023)

Spatial characterization of forest ecosystem services and human-induced complexities in Himalayan biodiversity hotspot area - Stutee Gupta; Srishti Gwal; Sarnam Singh (Environmental Monitoring and Assessment, 2023)

Xylitol: Production strategies with emphasis on biotechnological approach, scale up, and market trends - Srishti Mathur; Dinesh Kumar; Vinod Kumar; Adriana Dantas; Rachna Verma; Kamil Kuca (Sustainable Chemistry and Pharmacy, 2023)

Ochrobactrum sp. NBRISH6 Inoculation Enhances Zea mays Productivity, Mitigating Soil Alkalinity and Plant Immune Response - Shashank Kumar Mishra; Sankalp Misra; Vijay Kant Dixit; Srishti Kar; Puneet Singh Chauhan (Current Microbiology, 2023)

Prognostic Potential of Thrombocyte Indices, Acute Phase Proteins, Electrolytes and Acid-Base Markers in Canine Parvovirus Infected Dogs With Systemic Inflammatory Response Syndrome - Babul Rudra Paul; Ujjwal Kumar De; Varun Kumar Sarkar; Jitendra Singh Gandhar; Manas Kumar Patra; Mithilesh Kumar Singh; Srishti Soni; Chethan Gollahalli Eregowda (Topics in Companion Animal Medicine, 2023)

Chitosan-carbon nanofiber based disposable bioelectrode for electrochemical detection of oxytocin - Srishti Mehrotra; Pawankumar Rai; Krishna Gautam; Apoorva Saxena; Rahul Verma; Vaibhavi Lahane; Sakshi Singh; Akhilesh K. Yadav; Satyakam Patnaik; Sadasivam Anbumani; Smriti Priya; Sandeep K. Sharma (Food Chemistry, 2023)

Spatiotemporal variability and health risk assessment of PM2.5 and NO2 over the Indo-Gangetic Plain: A three years long study (2019-21) - Vikas Goel; Ajit Kumar; Srishti Jain; Vikram Singh; Mayank Kumar (Environmental Monitoring and Assessment, 2023)

Laboratory testing methods to evaluate the reliability of occupancy sensors for commercial building applications - Behlul Kula; Debrudra Mitra; Yiyi Chu; Kristen Cetin; Ryan Gallagher; Srishti Banerji (Building and Environment, 2023)

Ecological and health risk assessment of different land uses along with seasonal variation in toxic metal contamination around Varanasi city situated in Indo-Gangetic Plain - Srishti Mishra; Bhavna Jaiswal; S. B. Agrawal; Madhoolika Agrawal (Environmental Geochemistry and Health, 2023)

Effect of systemic inflammatory response syndrome on thrombocytogram, acute phase proteins, electrolytes, acid-base indices and cytokine expression in naturally canine parvovirus infected dogs - Babul R. Paul; Ujjwal K. De; Varun K. Sarkar; Jitendra S. Gandhar; Manas K. Patra; Ravi K. Agrawal; Mithilesh K. Singh; Srishti Soni; Chethan G. Eregowda (Veterinary Immunology and Immunopathology, 2023)

Revisiting Turcotte’s approach: flood frequency analysis - Witold F. Krajewski; Lindsay Otto; Srishti Vishwakarma; Gabriel Perez (Stochastic Environmental Research and Risk Assessment, 2023)
Flood frequency estimation forms the basis for engineering design of hydraulic structures, including bridges and culverts, local and regional development planning, and flood insurance. In the United States, the Water Resources Council recommends using the Log-Pearson Type III (LP3) distribution as a standard for use with the annual peak flow data. However, researchers have argued for the use of more than one streamflow value in a year thus increasing the sample size and decreasing the sampling error in the estimates of the flood quantiles. In this study, conducted over Iowa, the authors revisit the method proposed by Donald Turcotte and others to use power-law distribution applied to streamflow peak values for events separated by a time window. In contrast to those earlier studies, the authors applied formal statistical approach based on the maximum likelihood method and Kolmogorov-Smirnov statistic for parameter estimation. They also propose a novel simulation framework for the estimation of the sampling uncertainty of the power-law distribution. They apply the methodology to streamflow data from 62 USGS stream gauges in Iowa. The key finding of the study is that low-probability quantile estimates using Turcotte’s method result in conservative estimates when compared with LP3 distribution confirming the earlier outcomes.

Heavy metal remediation using chelator-enhanced washing of municipal solid waste compost based on spectroscopic characterization - Srishti Khare; Anupam Singhal; Saumitra Rai; Srinivas Rallapalli (Environmental Science and Pollution Research, 2023)

Sensor-integrated biocomposite membrane for food quality assessment - Pawankumar Rai; Suryansh Verma; Srishti Mehrotra; Smriti Priya; Sandeep K. Sharma (Food Chemistry, 2023)

Polylactic acid/tapioca starch/banana peel-based material for colorimetric and electrochemical biosensing applications - Pawankumar Rai; Srishti Mehrotra; Krishna Gautam; Aditya K. Kar; Apoorva Saxena; Satyakam Patnaik; Sadasivam Anbumani; Ashok Pandey; Smriti Priya; Sandeep K. Sharma (Carbohydrate Polymers, 2023)

Early-Life Intervention of Lactoferrin and Probiotic in Suckling Piglets: Effects on Immunoglobulins, Intestinal Integrity, and Neonatal Mortality - Varun Kumar Sarkar; Ujjwal Kumar De; Anju Kala; Ashok Kumar Verma; Anuj Chauhan; Babul Rudra Paul; Srishti Soni; Jitendra Singh Gandhar; Pallab Chaudhuri; Manas Kumar Patra; Chethan Gollahalli Eregowda; Gyanendra Kumar Gaur (Probiotics and Antimicrobial Proteins, 2023)

Diagnosis of GCM-RCM-driven rainfall patterns under changing climate through the robust selection of multi-model ensemble and sub-ensembles - Srishti Gaur; Rajnish Singh; Arnab Bandyopadhyay; Rajendra Singh (Climatic Change, 2023)

Feasibility and potential of laccase-based enzyme in wastewater treatment through sustainable approach: A review - Priya Sutaoney; Srishti Pandya; Devashri Gajarlwar; Veenu Joshi; Prabir Ghosh (Environmental Science and Pollution Research, 2022)

Geoalkalibacter halelectricus SAP ‐1 sp. nov. possessing extracellular electron transfer and mineral‐reducing capabilities from a haloalkaline environment - Sukrampal Yadav; Ramandeep Singh; Shiva S. Sundharam; Srishti Chaudhary; Srinivasan Krishnamurthi; Sunil A. Patil (Environmental Microbiology, 2022)
The extracellular electron transfer (EET)‐capable electroactive microorganisms (EAMs) play crucial roles in mineral cycling and interspecies electron transfer in different environments and are used as biocatalysts in microbial electrochemical technologies. Studying EAMs from extreme environments is desired to advance the electromicrobiology discipline, understanding their unique metabolic traits with implications to extreme microbiology, and develop specific bioelectrochemical applications. Here, we present a novel haloalkaliphilic bacterium named Geoalkalibacter halelectricus SAP‐1, isolated from a microbial electroactive biofilm enriched from the haloalkaline lake sediments. It is a rod‐shaped Gram‐negative heterotrophic anaerobe that uses various carbon and energy sources and respires on soluble and insoluble terminal electron acceptors. Besides 16S‐rRNA and whole‐genome sequence‐based phylogeny, the GGDC values of 21.7%, ANI of 78.5%, and 2.77% genomic DNA GC content difference with the closest validly named species Geoalkalibacter ferrihydriticus (DSM 17813 T ) confirmed its novelty. When grown with the solid‐state electrode as the only electron acceptor, it produced 460 ± 23 μA/cm 2 bioelectrocatalytic current, thereby confirming its electroactivity. Further electrochemical analysis revealed the presence of membrane redox components with a high formal potential, putatively involved in the direct mode of EET. These are distinct from EET components reported for any known electroactive microorganisms, including well‐studied Geobacter spp., Shewanella spp., and Desulfuromonas acetexigens . The capabilities of G . halelectricus SAP‐1 to respire on soluble and insoluble electron acceptors including fumarate, SO 4 2− , Fe 3+ , and Mn 4+ suggests its role in cycling these elements in haloalkaline environments.

Development of Novel Solid Nanostructured Lipid Carriers for Bioavailability Enhancement Using a Quality by Design Approach - Neha Bajwa; Shipra Mahal; Srishti Naryal; Preet Amol Singh; Ashish Baldi (AAPS PharmSciTech, 2022)

Habitat Adaptation Mediates the Influence of Leaf Traits on Canopy Productivity: Evidence from a Tropical Freshwater Swamp Forest - Weng Ngai Lam; Pin Jia Chan; Ying Ying Ting; Hong Jhun Sim; Jun Jie Lian; Rie Chong; Nur Estya Rahman; Lorraine Wen Ai Tan; Qian Yi Ho; Zhongyu Chiam; Srishti Arora; Hao Ran Lai; et al. (Ecosystems, 2022)

Desulfovulcanus ferrireducens gen. nov., sp. nov., a thermophilic autotrophic iron and sulfate-reducing bacterium from subseafloor basalt that grows on akaganéite and lepidocrocite minerals - Srishti Kashyap; Masroque Musa; Kaylee A. Neat; Deborah A. Leopo; James F. Holden (Extremophiles, 2022)
A deep-sea thermophilic bacterium, strain Ax17 T , was isolated from 25 °C hydrothermal fluid at Axial Seamount. It was obligately anaerobic and autotrophic, oxidized molecular hydrogen and formate, and reduced synthetic nanophase Fe(III) (oxyhydr)oxide minerals, sulfate, sulfite, thiosulfate, and elemental sulfur for growth. It produced up to 20 mM Fe 2+ when grown on ferrihydrite but < 5 mM Fe 2+ when grown on akaganéite, lepidocrocite, hematite, and goethite. It was a straight to curved rod that grew at temperatures ranging from 35 to 70 °C (optimum 65 °C) and a minimum doubling time of 7.1 h, in the presence of 1.5–6% NaCl (optimum 3%) and pH 5–9 (optimum 8.0). Phylogenetic analysis based on 16S rRNA gene sequences indicated that the strain was 90–92% identical to other genera of the family Desulfonauticaceae in the phylum Pseudomonadota . The genome of Ax17 T was sequenced, which yielded 2,585,834 bp and contained 2407 protein-coding sequences. Based on overall genome relatedness index analyses and its unique phenotypic characteristics, strain Ax17 T is suggested to represent a novel genus and species, for which the name Desulfovulcanus ferrireducens is proposed. The type strain is Ax17 T (= DSM 111878 T = ATCC TSD-233 T ).

Unexplored Excipients in Biotherapeutic Formulations: Natural Osmolytes as Potential Stabilizers Against Thermally Induced Aggregation of IgG1 Biotherapeutics - Purva P. Bhojane; Srishti Joshi; Sushree Jagriti Sahoo; Anurag S. Rathore (AAPS PharmSciTech, 2021)

Assessment of municipal solid waste management system in Lae City, Papua New Guinea in the context of sustainable development - Willie Doaemo; Sahil Dhiman; Alexander Borovskis; Wenlan Zhang; Sumedha Bhat; Srishti Jaipuria; Mirzi Betasolo (Environment, Development and Sustainability, 2021)

Projecting land use growth and associated impacts on hydrological balance through scenario-based modelling in the Subarnarekha basin, India - Srishti Gaur; Arnab Bandyopadhyay; Rajendra Singh (Hydrological Sciences Journal, 2021)

Dental Fluorosis and Periodontium: an Original Research Report of In Vitro and In Vivo Institutional Studies - K. L. Vandana; B. Srishti Raj; Rajendra Desai (Biological Trace Element Research, 2021)

Thiopeptides encoding biosynthetic gene clusters mined from bacterial genomes - Eshani Aggarwal; Srishti Chauhan; Dipti Sareen (Journal of Biosciences, 2021)

From Changing Environment to Changing Extremes: Exploring the Future Streamflow and Associated Uncertainties Through Integrated Modelling System - Srishti Gaur; Arnab Bandyopadhyay; Rajendra Singh (Water Resources Management, 2021)

Investigating the seasonal variability in source contribution to PM2.5 and PM10 using different receptor models during 2013–2016 in Delhi, India - Srishti Jain; Sudhir Kumar Sharma; Narayanswami Vijayan; Tuhin Kumar Mandal (Environmental Science and Pollution Research, 2021)

Spatio-temporal analysis of land use and land cover change: a systematic model inter-comparison driven by integrated modelling techniques - Srishti Gaur; Ateeksha Mittal; Arnab Bandyopadhyay; Ian Holman; Rajendra Singh (International Journal of Remote Sensing, 2020)

Understanding forest biomass and net primary productivity in Himalayan ecosystem using geospatial approach - Srishti Gwal; Sarnam Singh; Stutee Gupta; Shikha Anand (Modeling Earth Systems and Environment, 2020)

Hurst exponent approach through rescaled range analysis to study the time series of summer monsoon rainfall over northeast India - Srishti Pal; Shrutinil Dutta; Tamanna Nasrin; Surajit Chattopadhyay (Theoretical and Applied Climatology, 2020)

Wastewater treatment by slow sand filters using uncoated and iron-coated fine sand: impact of hydraulic loading rate and media depth - Srishti Verma; Achlesh Daverey; Archana Sharma (Environmental Science and Pollution Research, 2019)

Cancer incidence in the Agricultural Health Study after 20 years of follow-up - Catherine C. Lerro; Stella Koutros; Gabriella Andreotti; Dale P. Sandler; Charles F. Lynch; Lydia M. Louis; Aaron Blair; Christine G. Parks; Srishti Shrestha; Jay H. Lubin; Paul S. Albert; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2019)

Source Apportionment of PM10 Over Three Tropical Urban Atmospheres at Indo-Gangetic Plain of India: An Approach Using Different Receptor Models - Srishti Jain; Sudhir Kumar Sharma; Manoj Kumar Srivastava; Abhijit Chaterjee; Rajeev Kumar Singh; Mohit Saxena; Tuhin Kumar Mandal (Archives of Environmental Contamination and Toxicology, 2019)

Seasonal and annual trends of carbonaceous species of PM10 over a megacity Delhi, India during 2010–2017 - S. K. Sharma; T. K. Mandal; A. Sharma; Saraswati; Srishti Jain (Journal of Atmospheric Chemistry, 2018)

Carbonaceous and inorganic species in PM10 during wintertime over Giridih, Jharkhand (India) - S. K. Sharma; T. K. Mandal; A. K. De; N. C. Deb; Srishti Jain; Mohit Saxena; S. Pal; A. K. Choudhuri; Saraswati (Journal of Atmospheric Chemistry, 2018)

Carbonaceous Species of PM2.5 in Megacity Delhi, India During 2012–2016 - S. K. Sharma; T. K. Mandal; A. Sharma; Srishti Jain; Saraswati (Bulletin of Environmental Contamination and Toxicology, 2018)

Occupational exposure to perfluoroalkyl substances and serum levels of perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in an aging population from upstate New York: a retrospective cohort study - Eva M. Tanner; Michael S. Bloom; Qian Wu; Kurunthachalam Kannan; Recai M. Yucel; Srishti Shrestha; Edward F. Fitzgerald (International Archives of Occupational and Environmental Health, 2018)

Spectral and morphological characteristics of synthetic nanophase iron (oxyhydr)oxides - Elizabeth C. Sklute; Srishti Kashyap; M. Darby Dyar; James F. Holden; Thomas Tague; Peng Wang; Steven J. Jaret (Physics and Chemistry of Minerals, 2018)

Chemical characteristics and source apportionment of PM2.5 using PCA/APCS, UNMIX, and PMF at an urban site of Delhi, India - Srishti Jain; Sudhir Kumar Sharma; Nikki Choudhary; Renu Masiwal; Mohit Saxena; Ashima Sharma; Tuhin Kumar Mandal; Anshu Gupta; Naresh Chandra Gupta; Chhemendra Sharma (Environmental Science and Pollution Research, 2017)

Spatio-temporal variation in chemical characteristics of PM10 over Indo Gangetic Plain of India - S. K. Sharma; T. K. Mandal; M. K. Srivastava; A. Chatterjee; Srishti Jain; M. Saxena; B. P. Singh; Saraswati; A. Sharma; A. Adak; S. K.Ghosh (Environmental Science and Pollution Research, 2016)

Source Apportionment of PM2.5 in Delhi, India Using PMF Model - S. K. Sharma; T. K. Mandal; Srishti Jain; Saraswati; A. Sharma; Mohit Saxena (Bulletin of Environmental Contamination and Toxicology, 2016)

Antihyperglucolipidaemic and anticarbonyl stress properties in green, yellow and red sweet bell peppers ( Capsicum annuum L.) - Srishti Shukla; Dommati Anand Kumar; Sanga Venkata Anusha; Ashok Kumar Tiwari (Natural Product Research, 2016)

Hypocretin/orexin antagonism enhances sleep-related adenosine and GABA neurotransmission in rat basal forebrain - Jacqueline Vazquez-DeRose; Michael D. Schwartz; Alexander T. Nguyen; Deepti R. Warrier; Srishti Gulati; Thomas K. Mathew; Thomas C. Neylan; Thomas S. Kilduff (Brain Structure and Function, 2016)